Implementasi Kerjasama Pelayanan JAMKESDA Antara Kabupaten Semarang dan Kota Salatiga - Inggarrini Raditetyastuti; Wiwik Widayati; Sulistyowati . (Journal of Politic and Government Studies, 2015)
Public services is a service which provided by the government to all the community without exception. The effort to enhance public services is done with this regional cooperation, one of them in the health sector. Local governments creating a health care program called on regional health insurance ( JAMKESDA ) is guarantee for the payment of health services provided by the government. The purpose of this research is to know the implementation of cooperation between Semarang district and Salatiga city and knowing factors that hampers in JAMKESDA service performance in the city of Salatiga.As the material for know as well of the implementation of factors that hampers JAMKESDA services in the city of Salatiga then collection of data using a technique interview to interviews speakers and people who controlled the implementation of JAMKESDA services as well as the documents in the form of writing, a picture, the note, a transcript of that and so on. The qualitative descriptive analysis of type data analysis is chosen to examine the available data from many sources. From the outcome of research known that the implementation of cooperation in health JAMKESDA services between the government of the Semarang district and Salatiga City not running smoothly. There are several factors that block, among of them are JAMKESDA system which somewhat complicated, the limit budget and deficient of the coordination among employers who involved in the JAMKESDA service.